Income-related inequity in the use of GP services: A comparison of Ireland and Scotland - Richard Layte; Anne Nolan (The Economic and Social Research Institute (ESRI), 2013)
Equity of access to health care is a key component of national and international health policy. The Irish health-care system is unusual in requiring the majority of the population to pay the full cost of GP care at the point of use. In contrast, all Scottish residents are entitled to free GP care at the point of use. Using nationally representative micro-data on Irish and Scottish children, we find that the distribution of GP care in Ireland favours those on lower incomes (i.e., 'pro-poor'), but that there is no significant difference in the distribution of GP care across income groups in Scotland. Focusing just on children who pay for GP care in Ireland, we find some evidence for a significant 'pro-rich' distribution of GP visits.
Keywords: C20; D12; I10; 330; GP Services; Children; Concentration Index; Inequity; Ireland; Scotland